2018
DOI: 10.1038/s41598-018-22097-z
|View full text |Cite
|
Sign up to set email alerts
|

Super anticorrosion of aluminized steel by a controlled Mg supply

Abstract: The current anticorrosion strategy makes use of coatings to passively protect the steel, which faces increasing challenge due to the tightened environmental regulations and high cost. This paper reports a new method for achieving a super anticorrosion function in Al-Si alloys through Mg nano-metallurgy, which was characterized by real-time synchrotron measurements. The unique function is based on the formation of an amorphous and self-charge-compensated MgAl2O4-SiO2 phase between the grain boundaries to help p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…So far, several studies have been reported about the corrosion resistance of Al, Mg, and Zn films prepared by the PVD method. Jeong et al explained that the Mg layer deposited by the PVD method prevents the penetration of oxygen species by forming Mg corrosion products at the grain boundary of the base material [10,18]. La and Park et al showed the effectiveness of the Zn-Mg coating layer on corrosion resistance regarding the formation of protective corrosion products [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have been reported about the corrosion resistance of Al, Mg, and Zn films prepared by the PVD method. Jeong et al explained that the Mg layer deposited by the PVD method prevents the penetration of oxygen species by forming Mg corrosion products at the grain boundary of the base material [10,18]. La and Park et al showed the effectiveness of the Zn-Mg coating layer on corrosion resistance regarding the formation of protective corrosion products [19,20].…”
Section: Introductionmentioning
confidence: 99%